Primary Testicular Failure with Unilateral Cryptorchidism - Ahmad Ricardo Silalahi; Tjahjo Djojo Tanojo; Reny I'tishom (Indonesian Andrology and Biomedical Journal, 2020)
Background: Primary Testicular Failure (PTF) in men with unilateral cryptorchidism is a rare case, which might be the first time reported. Case: A 34-year-old man came with infertility and azoospermia. Signs of secondary sex found. FSH levels: 60.68 mIU / ml, LH levels: 15.96 mIU / ml, T levels: 336.14 ng / dl, E2 levels: 27.81 ng / dl. Ultrasound showed the left testis in the left inguinal +/- 2,4x1,1x3,6 cm in size, with decrease vascularization; +/- 4.1 cm from the base of the penis. The right testis size +/- 2,8x1,1x2,2 cm in the right scrotum accompanied by spermatocele. The patient was referred to the Urology department for orchidopexy of the left testis in the inguinal. Discussion: Primary testicular failure, in this case, may occur due to idiopathic but does not rule out the mosaic type of Klinefelter syndrome. The patient has unilateral cryptorchidism for 20 years, there will be a risk of testicular cancer. Management of cryptorchidism must be performed orchidopexy the first year after birth. After orchidopexy, monitoring is needed every year until at least 5 years. Conclusion: PTF occurs when the parenchymal tissue contained in the testes is no longer able to produce sperm or testosterone. PTF diagnosis is only possible through pathology and testicular cytology, but the combination of FSH and Inhibin B examination remains the best recommendation as a biomarker for patients with PTF.